Quantitative Reconstruction of a Disturbed Ultrasound Pressure Field in a Conventional Hydrophone Measurement - Chen, Lizhuo; Rupitsch, Stefan; Lerch, Reinhard (IEEE Transactions on Ultrasonics Ferroelectrics and Frequency Control, 2013)
Among various techniques enabling absolute measurements of ultrasound pressure, light refractive tomography (LRT) is so far the only one which is noninvasive, omnidirectional, and provides time-resolved results in pascals. By exploiting all these advantages, LRT shows suitability for investigations of ultrasound pressure fields, even in the case of adjacent medium boundaries which may cause considerable sound reflections. To demonstrate the potential research possibilities offered by this technique, we apply LRT to investigating the disturbance to a pressure field caused by a hydrophone. A commercial capsule hydrophone is placed in front of an ultrasound transducer excited by 1-MHz burst signals. We reconstruct the disturbed ultrasound pressure field between the hydrophone and the transducer in both spatial and temporal dimensions. Good agreement has been achieved between the reconstructed pressure field and the prediction made by a numerical simulation. Moreover, a comparison between the results provided by LRT and hydrophone shows that multiple reflections can jeopardize the reliability of hydrophone measurement when a hydrophone is placed very close to a medium boundary (e. g., <5 mm in our case). On the contrary, LRT achieves reasonable results at all distances. Finally, as a proof of the reliability of LRT, we compare the pressure amplitudes offered by LRT and hydrophone measurements at 27 mm away from the transducer in the absence of obstacles. The comparison shows a relative difference of 7.07%.